PENGARUH STRUKTUR AKTIVA, RISIKO BISNIS, PERTUMBUHAN PENJUALAN, DAN PROFITABILITAS TERHADAP STRUKTUR MODAL - Sari, Retno Indah; Ardini, Lilis (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThe purpose of this research is to find out the influence of assets structure to the capital structure, the influence of business risk to the capital structure, the influence of sales growth to the capital structure, and the influence of profitability to the capital structure. The population is a consumer goods companies which are listed in Indonesia Stock Exchange during 4 years observation period from 2012 to 2015. The sample collection technique has been carried out by using purposive sampling, and 28 consumer goods companies have been selected as samples. The analysis technique has been done by using multiple linear regression and hypothesis testing. The result of the analysis of the model feasibility test shows that asset structure, business risks, sales growth and profitability give significant influence to the capital structure of consumer goods companies which are listed in Indonesia Stock Exchange. Partially, the result of the research shows that assets structure give significant and positive influence to the capital structure, business risk does not give significant and negative influence to the capital structure, sales growth give significant and positive influence to the capital structure and profitability give significant and negative influence to the capital structure.Keywords: Asset structure, business risk, sales growth, profitability, capital structure.